Quantum effects in the thermal conductivity of solid krypton—methane solutions: Low-Temperature Thermodynamics and Structure - Krivchikov, A.I.; Gorodilov, B.Ya.; Manzhelii, V.G.; Dudkin, V.V. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2003)
The dynamic interaction of a quantum rotor with its crystalline environment has been studied by measurement of the thermal conductivity of the Kr1–c(CH4)c solid solutions at c = 0.05–0.75 in the temperature region 2–40 K. The thermal resistance of the solutions was mainly determined by the resonance scattering of phonons on CH4 molecules with the nuclear spin I = 1 (the nuclear spin of the T species). The influence of the nuclear spin conversion on the temperature dependence of the thermal conductivity к(T) leads to a well-defined minimum on к(T). The temperature of the minimum depends on the CH4 concentration. It was shown that the nonmonotonic increase of the anisotropic molecular field with the CH4 concentration is caused by a compensation effect due to corrections in the mutual orientations of the neighboring rotors at c > 0.5. The temperature dependence of Kr1–c(CH4)c is described within the Debye model of thermal conductivity taking into account the lower limit of the phonon mean free path. It is shown that phonon–rotation coupling is responsible for the anomalous temperature dependence of the thermal resistance at varying temperature. It increases strongly when the quantum character of the CH4 rotation at low temperatures changes to a classical one at high temperatures. A thermal conductivity jump (a sharp increase in к(T) within a narrow temperature range) was also observed. The temperature position of the jump varies from 9.7 to 8.4 K when the CH4 concentration changes from 0.25 to 0.45.